Opre Roma! // Up, Romanies! : A Thematic Analysis of Appearance, Voice and Agency of Romani Media Activists’ Platforms in Sweden - Noe,Leonie (2020)
This research is concerned with Romani media activists’ use of different online platforms in order to counter the stereotypical representation of Roma in dominant discourses, such as in mass media and state policies. Links are made between these platforms and the cultural context of Sweden that they are set in. Additionally, the following explores these platforms in connection to collective identity and civic agency for the Romani community in Sweden. This research takes the standpoint that media and communication play a significant role in the discourses that are created around Roma, and that these discourses have material consequences that impact the lives of Roma. Therefore, the significance of Roma having agency and power over their own platforms, narratives and discourses is underlined. The empirical data of this research is gathered through semi-structured interviews with Romani media activists and triangulated with articles published on the Romani web magazine Dikko. Both sources of data have been thematically analyzed and brought into context of relevant research, orbiting around the themes of othering and dehumanization, and agency, appearance and voice. The analysis is divided in three sections: The first creates an overview of the Romani platforms and affordances, which the media activists make use of according to the goals they try to achieve. Three different strategies employed through these platforms are examined, which portray the agency of Roma: Countering the dominant discourse, voicing concrete demands and employing emotions, such as anger. The second section goes deeper into two perceived cultural attributes. Firstly, that support to Roma is given in theory, but not put into practice. Secondly, that racism against Roma is met with silence and passivism in the Swedish society. The last section explores the impact of the platforms offering a space for Roma to have a collective identity that exists across past, present and future, giving a sense of durability as a people. This section concludes with a discussion on potential impact and voice through the Romani media activism. There seems to be a remaining lack of research on the mediation of Roma as active agents and multifaceted humans, as opposed to the existing research around the representation of Roma as victim, passive and criminals. This study comes to the conclusion that the Romani media platforms have an empowering function for the activists and serve as a tool in their struggle to gain an effective voice. Further research in this field is suggested in order to assure a more appropriate space for minorities in the media world; a space where Roma are represented as human beings.
Keywords: Romani Media Activism; Media Activism; Collective Agency; Silence; Structural Discrimination; Othering; Dehumanization; Voice; Appearance; Historicity; Decoloniality; Thematic Analysis; Semi-Structured Interviewing; Sweden